Critical thinking skills profile of high school students in learning chemistry - Budi Utami; Sulistyo Saputro; Ashadi Ashadi; Mohammad Masykuri; Sri Widoretno (International Journal of Science and Applied Science: Conference Series, 2017)
Critical thinking skill is the priority in the goals of education. In this case, the critical thinking has the higher process, such as analyzing, synthesizing, evaluating, drawing conclusion and reflecting which enables the individual to make the reasonable assessment both in the classroom and in the daily life.  This research is aimed to determine the students’ critical thinking skill in learning Chemistry at senior high school. This research used descriptive method in which the instruments were developed based on the indicators of critical thinking skill. The population of this research was 100 students of tenth, eleventh and twelfth grade from senior high schools in Surakarta which was chosen using cluster random sampling technique. The result of the research shows that the students of tenth, eleventh and twelfth grade have adequate critical thinking skills.